Transcriptome profiling of differentially expressed genes in floral buds and flowers of male sterile and fertile lines in watermelon. (December 2015) - Rhee, Sun-Ju; Seo, Minseok; Jang, Yoon-Jeong; Cho, Seoae; Lee, Gung
Abstract Background Male sterility is an important mechanism for the production of hybrid seeds in watermelon. Although fruit development has been studied extensively in watermelon, there are no reports on gene expression in floral organs. In this study, RNA-sequencing (RNA-seq) was performed in two near-isogenic watermelon lines (genic male sterile [GMS] line, DAH3615-MS and male fertile line, DAH3615) to identify the differentially expressed genes (DEGs) related to male sterility. Results DEG analysis showed that 1259 genes were significantly associated with male sterility at a FDRP -value of < 0.01. Most of these genes were only expressed in the male fertile line. In addition, 11 functional clusters were identified using DAVID functional classification analysis. Of detected genes in RNA-seq analysis, 19 were successfully validated by qRT-PCR. Conclusions In this study, we carried out a comprehensive floral transcriptome sequence comparison of a male fertile line and its near-isogenic male sterile line in watermelon. This analysis revealed essential genes responsible for stamen development, including pollen development and pollen tube elongation, and allowed their functional classification. These results provided new information on global mechanisms related to male sterility in watermelon.